Trade Credit, Financial Intermediary Development, and Industry Growth - Fisman, Raymond; Love, Inessa (World Bank, Washington, DC, 2014)
Recent empirical work has shown that financial development is important for economic growth, since well-developed financial markets are more effective at allocating capital to firms with high-value projects. This raises the question of whether firms with high return projects in countries with poorly developed financial institutions, are able to draw on alternative sources of capital, to offset the effects of deficient (formal) financial intermediaries. Recent work suggests that implicit borrowing, in the form of trade credit, may provide one such source of funds. Using the methodology of Rajan and Zingales (1998), the authors show that in countries with relatively weak financial institutions, industries with greater dependence on trade credit financing (measured by the ratio of accounts payable to total assets) grow faster than industries that rely less on such credit. Furthermore, consistent with the notion that young firms may not use trade credit, the authors show that most of the effect they report, comes from growth in preexisting firms, rather than from an increase in the number of firms.